Schistosomiasis Burden and Its Association With Lower Measles Vaccine Responses in School Children From Rural Cameroon - Nono, Justin Komguep; Kamdem, Severin Donald; Netongo, Palmer Masumbe; Dabee, Smritee; Schomaker, Michael; Oumarou, Alim; Brombacher, Frank; Moyou-Somo, Roger (Frontiers in Immunology, 2018)
Background and Methods: Schistosomiasis is debilitating and reported to impair immune responsiveness of infected hosts. In Cameroon, mass drug administration (MDA) is used in schoolchildren to reduce transmission of S. haematobium and S. mansoni. The effects of MDA and the impact of schistosomiasis on the titers of antibodies in vaccinated children have been poorly studied. We therefore assessed the prevalence of schistosomiasis in schoolchildren, eight months after MDA, in two locations: Barombi Koto (BK), endemic for S. haematobium (N =169) and Yoro (Y), endemic for S. mansoni (N = 356). Age, gender, residence time and frequency of contact with river water were assessed as risk factors for infection and morbidity in both localities. In 70 schoolchildren from BK and 83 from Y, ultrasound was used to assess morbidity according to the WHO guidelines. Evaluation of measles antibodies was performed in previously vaccinated schoolchildren (14 with S. haematobium and 12 egg-negative controls from BK and 47 with S. mansoni and12 egg-negative controls from Y). Principal Findings and conclusions: The prevalence of S. haematobium was 25.4% in BK (43/169) and 34.8% for S. mansoni in Y (124/356), indicating the persistent transmission of schistosomiasis despite MDA. Older age (AOR 1.31; 95%CI 1.12-1.54) and higher frequencies of exposure to river water (AOR 1.99; 95%CI 1.03-3.86) were identified as risks for infection in BK whereas only older age (OR 1.15; 95%CI 1.04-1.27) was a risk for infection in Y. Bladder pathology (score 2 to 5) was observed in 29.2% (7/24) of egg-positive children in BK and liver pathology (pattern C) in 31.1% (19/61) of egg-positive children in Y. There was a positive correlation between S. haematobium egg burden and bladder pathology (AOR 1.01; 95%CI 0.99-1.02) and positive correlation between S. mansoni-driven liver pathology and female gender (AOR 3.01; 95%CI 0.88-10.26). Anti-measles antibodies in vaccinated children were significantly lower in S. mansoni-infected when compared to egg-negative controls ((p=0.001), which was not observed in the S. haematobium-infected group from BK. Our results demonstrate a questionable efficacy of MDA alone in halting schistosomiasis transmission and confirm a possible immunomodulatory effect of S. mansoni on response to vaccines.